War for the peace in Pakistan - Ali, Syed Masroor; Abdul Rahim, Aidil Faszrul (2013)
Pakistan because of its geographical location became a front line state in the war against terror since the attack on the World Trade Centre on September 11, 2001. Pakistan decided to align with USA to combat the so-called fundamentalist and Islamic terrorist. Currently, the biggest threat to the state and citizens is the killing of innocent civilians in suicidal and other attacks. It’s a war whose main purpose is to save people from terrorism. Now lives of Pakistan’s own citizens are at stake. Innocent people have become the targets of deadly bombs. It has resulted in much more loss of lives than 9/11 attack. Moreover, law and order situation in the country has constantly deteriorated since 2001.One obvious and tragic price of this open war is the toll of death and destruction. There is an additional cost, a psychological cost borne by the survivors of war and socio-economic pressure. The civilian victims of war may suffer the greatest psychological harm, for they have not been prepared to manage the stress, shock, and fright of violence. The civilian population, who were drawn away from their safe surroundings and the children who have lost their parents in this war are the real casualties we need to take into consideration. It’s a matter of concern for understanding and discussing these issues from various perspectives, including an Islamic perspective. This poster will highlight the psycho-social aspects of war which could not achieved peace yet.